Investigation of abnormal histology and cytology of cervix - N Asnafi (Babol University of Medical Sciences, 2004)
Background and Objective: Pap smear is the first diagnostic step of pre-invasive lesion. Its sensitivity is 85%. Colposcopic and histologic evaluation for diagnosis is recommended. The aim of this study was to compare abnormal cytologic and histologic findings. Methods: This cross-sectional study was done on the patients who referred to obstetrics and gynecologic clinic of Babol Yahyanejad hospital. In patients with abnormal cytology, cervical biopsy with colposcopic examination was performed. Findings: Among 7050 patients, 74 (1.04% cases had shown abnormal Pap smear that 58 (79%) were with reactive atypia and 21% were with cancerous and invasive lesions. Prevalence of cancerous lesion was 0.22%. Abnormal histologic results were in 9 (12.2%) cases (LSIL 5.4%, HSIL 1.4%, carcinoma 5.4%). There was a significant correlation between cytologic and histologic findings (P<0.05). Conclusion: It is necessary to evaluate completely with colposcopy and cervical biopsy, when Pap smear is abnormal.